Specifics of Covert Investigative Activities in Criminal Proceedings - BEKISHEV, Askhat Kenzhebekovich; KAN, Aleksandr Gerasimovich; IBRAYEVA, Alua Salamatovna; DYUSSEBALIYEVA, Soledad Saginovna; IBRAYEV, Nurlan Salamatovich (Journal of Advanced Research in Law and Economics; Vol 10 No 1 (2019): JARLE Volume X Issue 1(39) Spring 2019DO - 10.14505//jarle.v10.1(39).08, 2019)
The article considers specific provisions related to the institute of covert investigative activities in the legislation of Kazakhstan. The authors of the article conducted a systematic analysis of the Kazakh legislation and law enforcement, which determines gaps and contradictions hindering the effective application of rules governing the use of covert investigative activities. In addition, the article discloses issues regarding the concept of covert investigative activities and its use in special legal literature. According to the study results, the current legislation of Kazakhstan regulating the procedure and grounds for conducting covert investigative activities requires some revision. The authors state that it is necessary to amend and supplement the Kazakh legislation, as well as increase the efficiency of law enforcement agencies conducting covert investigative activities in the course of crime investigation.